Comparison of medication adherence and satisfaction between entecavir and tenofovir alafenamide therapy in chronic hepatitis B. Issue 8 (7th February 2020) - Tamaki, Nobuharu; Kurosaki, Masayuki; Nakanishi, Hiroyuki; Itakura, Jun; Inada, Kento; Kirino, Sakura; Yamashita, Koji; Osawa, Leona; Sekiguchi, Shuhei; Hayakawa, Yuka; Wang, Wan; Okada, Mao; et al.
Abstract: Adherence to nucleotide/nucleoside analog therapy is important in improving prognosis in chronic hepatitis B. We aimed to compare medical adherence and satisfaction with entecavir (ETV) and tenofovir alafenamide (TAF) and to assess the effect of switching from ETV to TAF. Patients taking ETV (n = 114) and TAF (n = 35), and who switched from ETV to TAF (n = 15) were included. Medication adherence and satisfaction were assessed using a questionnaire. There was no significant difference in adherence between the ETV and TAF groups, but the medication satisfaction rates (0‐10, prefer‐dislike) were 1.72 ± 2.2 and 0.69 ± 1.5, respectively ( P  = .01; significantly higher in the TAF group). In patients who switched from ETV to TAF, medication adherence significantly improved ( P  = .04) as follows: never forgetting, from 40% to 87%; forgetting once every 2 to 3 months, from 33% to 7%; forgetting once every 2 months, from 20% to 7%, and forgetting once every 4 weeks, from 7% to 0%. Similarly, the medication satisfaction rate significantly improved from 4.53 ± 3.2 to 1.27 ± 2.4 after switching ( P  = .008). In conclusion, switching from ETV to TAF can be a useful approach to improve medication adherence and satisfaction. Highlights: TAF had a higher satisfaction score than ETV, and switching from ETV to TAF is effective in improving medication adherence and satisfaction.